Food deprivation among adults in India: an analysis of specific food categories, 2016-2021 - Anoop Jain; Smriti Sharma; Rockli Kim; S. V. Subramanian (Eclinical medicine, 2023)
Understanding the extent to which food groups are missing from an individual's diet is essential to understanding the extent to which they are undernourished.
Keywords: ANC; Health insurance; Institutional delivery; maternal health; PNC